Pengaruh Eksistensi Ekstrakurikuler Tahfidz terhadap Kecerdasan Intelektual Peserta Didik Kelas VI MI Muhammadiyah Ngadirejan - Nisa, Nisa; Ruhardi, Rudi; Agustiani, Happy (ISLAMIKA, 2024)
The existence of extracurricular tahfidz is a way for humans to express themselves or the potential that exists within them, so that their existence can be useful or meaningful through activities outside of lessons in order to help students develop their potential according to their interests and talents, one of which is extracurricular tahfidz (memorization). Problems that are often faced in extracurricular tahfidz are family factors, students' ability to read and memorize the Koran. This research aims to determine the extent of the influence of the existence of tahfidz extracurriculars on the intellectual intelligence of class VI students at MI Muhammadiyah Ngadirejan. This research is verification research with a quantitative approach. This research used a limited population, namely all MI Muhammadiyah Ngadirejan students with a total of 167 students. The sample used was class VI with a total of 30 students. The sampling technique is using random sampling (simple random sampling). Data collection techniques use questionnaires, interviews and observation. Instrument development uses validity and reliability tests. The data analysis technique in this research uses the classic assumption test and simple regression test and to answer the hypothesis uses the T test. Based on the research data analysis using the T test, the significance value of the influence of the existence of extracurricular tahfidz (X) on intellectual intelligence (Y) is 0.006 < 0, 05 and the calculated t value is 2.965 > t table value 2.048. This shows that the existence of extracurricular tahfidz has a partial influence on intellectual intelligence. And based on the coefficient of determination of extracurricular existence, Tahfidz has an influence on intellectual intelligence of 24% and the remaining 86% is influenced by other variables.